1998
DOI: 10.1084/jem.188.10.1785
|View full text |Cite
|
Sign up to set email alerts
|

HIV-1 Variation Diminishes CD4 T Lymphocyte Recognition

Abstract: Effective long-term antiviral immunity requires specific cytotoxic T lymphocytes and CD4+ T lymphocyte help. Failure of these helper responses can be a principle cause of viral persistence. We sought evidence that variation in HIV-1 CD4+ T helper epitopes might contribute to this phenomenon. To determine this, we assayed fresh peripheral blood mononuclear cells from 43 asymptomatic HIV-1+ patients for proliferative responses to HIV-1 antigens. 12 (28%) showed a positive response, and we went on to map dominant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
47
4

Year Published

2004
2004
2018
2018

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 65 publications
(52 citation statements)
references
References 28 publications
(40 reference statements)
1
47
4
Order By: Relevance
“…These results suggest, in contrast to other reports that have shown a negative effect of viral variation on CD4 T-cell recognition [26,27], that CD4 responses may be somewhat tolerant of viral variation. T-helper cells may have been reactive to more than one of the peptides in the cocktail, and although limitations of small blood volumes from the HIV-1 infected children in this study did not allow peptide responses to be tested individually, this approach would be important in future studies to provide more insight into immunogenic epitopes.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…These results suggest, in contrast to other reports that have shown a negative effect of viral variation on CD4 T-cell recognition [26,27], that CD4 responses may be somewhat tolerant of viral variation. T-helper cells may have been reactive to more than one of the peptides in the cocktail, and although limitations of small blood volumes from the HIV-1 infected children in this study did not allow peptide responses to be tested individually, this approach would be important in future studies to provide more insight into immunogenic epitopes.…”
Section: Discussioncontrasting
confidence: 99%
“…They observed that the interaction of gp120 epitopes with CD4 T-cell receptors and MHC is precise and poorly cross-reactive, with even one conservative substitution drastically reducing recognition. In another study, by Harcourt et al [27], PBMC from asymptomatic HIV-1 infected patients were assayed for proliferative responses to HIV-1 antigens. Two individuals who showed positive responses were further analysed, and a dominant CD4 T-lymphocyte response was localised to p17 Gag and p24 Gag epitopes, with proviral DNA sequencing revealing substantial sequence variation within both these peptide epitopes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the murine LCMV model, transgenic virus-specific CD4 + T cells selected for T helper epitope mutants that evaded recognition [44]. However, while viral evolution in CD4 + T cell epitopes in untreated HIV-1-infected persons abrogated T cell responses in vitro, viral variants did not have a clear survival advantage [45]. More recently, no variation in epitopes targeted by circulating IFN-c-secreting CD4 + T cells was detected by sequencing of plasma HIV-1 RNA, in a cross-sectional study of chronically infected untreated subjects [46].…”
mentioning
confidence: 99%
“…A hallmark of HIV infection is its ability to generate immune escape mutations in epitopes (14)(15)(16)(17) and their flanking regions (18,19). CTL escape mutants have been found in population studies, in which they correlate with higher viral loads (20), and they can be transmitted from mother to child (21,22) as well as between sexual partners (ref.…”
mentioning
confidence: 99%